2018
DOI: 10.1111/exsy.12328
|View full text |Cite
|
Sign up to set email alerts
|

HEARTDROID—Rule engine for mobile and context‐aware expert systems

Abstract: Building mobile context‐aware systems is inherently complex and non‐trivial task. It consists of several phases starting from acquisition of context, through modeling to execution of contextual models. Today, such systems are mostly implemented on mobile platforms, that introduce specific requirements, such as intelligibility, robustness, privacy, and efficiency. Over the last decade, along with the rapid development of mobile industry, many approaches were developed that unevenly support these requirements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…However, the development of large-scale rule-based systems may face numerous challenges. For instance, the reasoning process can be very complex, and designing of such systems becomes hard to manage [133]. There is still a lack of lightweight rule-based inference engines that will allow for reasoning on mobile devices [133].…”
Section: Research Issues and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of large-scale rule-based systems may face numerous challenges. For instance, the reasoning process can be very complex, and designing of such systems becomes hard to manage [133]. There is still a lack of lightweight rule-based inference engines that will allow for reasoning on mobile devices [133].…”
Section: Research Issues and Future Directionsmentioning
confidence: 99%
“…For instance, the reasoning process can be very complex, and designing of such systems becomes hard to manage [133]. There is still a lack of lightweight rule-based inference engines that will allow for reasoning on mobile devices [133]. Thus a set of concise and effective rules will be beneficial in terms of outcome and simplicity for such a rule-based expert system for mobile devices.…”
Section: Research Issues and Future Directionsmentioning
confidence: 99%
“…It uses the SPARQL Event Processing Architecture (SEPA) to perform SPARQL updates and queries on the underlying RDF graph, enabling to monitor the daily behaviour of people that face problems in home settings due to ageing or illnesses. HEARTDROID [ 44 ] uses a rule inference engine for Android mobile devices. It allows the definition of semantic annotations of its components in order to increase intelligence and transparency of the model and the reasoning services.…”
Section: Background and Related Workmentioning
confidence: 99%
“…We have demonstrated that it is straightforward to include emotional contexts in AmI systems built on top of HMR+ and HeaRTDroid [65], mainly due to the modularized nature of HMR+ models, which can be easily extended with additional knowledge. Figure 12 presents a simple HMR+ model for adapting a mobile phone ringtone to a temporal context; this example came from the tutorial for HeaRTDroid, and originally did not include the emotional context table.…”
Section: Interpretation Of Emotions Using Context-aware Systemsmentioning
confidence: 99%